THE IMPACT OF LANDINGS AND GROUND REACTION FORCES IN ARTISTIC GYMNASTICS: A SYSTEMATIC REVIEW - Beatriz Silva; Isaura Leite; Cristina Gomes; Manuel Campos; Filipa Sousa; Lurdes Ávila-Carvalho (Science of Gymnastics Journal)
There is growing concern about the technical execution of gymnastics landings due to the repeated impacts experienced by gymnasts and their potential consequences. Most artistic gymnastics exercises conclude with a landing, during which gymnasts are subjected to very high ground reaction forces. This review aimed to identify and synthesize the available scientific literature on landing techniques across different apparatuses in artistic gymnastics.